Learning From K-5 Teachers Who Think Aloud. Issue 3 (2nd July 2016) - Ness, Molly
ABSTRACT: An essential element in teaching children to effectively comprehend text is the use of teacher-led think-alouds. The overarching objective of this study was to explore how to better prepare early career teachers to conduct think-alouds in their classrooms. Data from 31 teachers consisted of (1) questionnaires, (2) lesson plans, (3) lesson transcripts, and (4) written reflections. Teachers made significant growth in the quantity and quality of reading comprehension strategies they incorporated. Discussion focuses on the challenges the participants encountered when thinking aloud. Finally, suggestions for supporting teachers in effectively thinking aloud are provided.